Properties of Interstellar Medium in Star-Forming Galaxies at z~1.4 revealed with ALMA - Seko, A; Ohta, K; Yabe, K; Hatsukade, B; Akiyama, M; Iwamuro, F; Tamura, N; Dalton, G (IOP Publishing, 2016)
We conducted observations of 12CO(J = 5-4) and dust thermal continuum emission toward 20 star-forming galaxies on the main sequence at z ∼ 1.4 using ALMA to investigate the properties of the interstellar medium. The sample galaxies are chosen to trace the distributions of star-forming galaxies in diagrams of stellar mass versus star formation rate and stellar mass versus metallicity. We detected CO emission lines from 11 galaxies. The molecular gas mass is derived by adopting a metallicity-dependent CO-to-H2 conversion factor and assuming a CO(5-4)/CO(1-0) luminosity ratio of 0.23. Masses of molecular gas and its fractions (molecular gas mass/(molecular gas mass + stellar mass)) for the detected galaxies are in the ranges of (3.9-12) × 1010 Mo and 0.25-0.94, respectively; these values are significantly larger than those in local spiral galaxies. The molecular gas mass fraction decreases with increasing stellar mass; the relation holds for four times lower stellar mass than that covered in previous studies, and the molecular gas mass fraction decreases with increasing metallicity. Stacking analyses also show the same trends. Dust thermal emissions were clearly detected from two galaxies and marginally detected from five galaxies. Dust masses of the detected galaxies are (3.9-38) × 107 Mo. We derived gas-to-dust ratios and found they are 3-4 times larger than those in local galaxies. The depletion times of molecular gas for the detected galaxies are (1.4-36) × 108 yr while the results of the stacking analysis show ∼3 × 108 yr. The depletion time tends to decrease with increasing stellar mass and metallicity though the trend is not so significant, which contrasts with the trends in local galaxies.